Policy Interventions Shaping HIV Prevention: Providers' Active Role in the HIV Continuum of Care. (October 2018) - Pinto, Rogério M.; Witte, Susan S.; Filippone, Prema L.; Choi, C. Jean; Wall, Melanie
The U.S. Centers for Disease Control and Prevention (CDC) Diffusion of Effective Behavioral Interventions project has disseminated HIV behavioral interventions (EBIs) across the United States since the 1990s. In 2011, the CDC launched the High-Impact HIV Prevention (HIP) project, providing EBIs plus high-impact services (HIV testing, primary care, and support services). Providers (nurses, social workers, educators) are unable to consistently make linkages; thus, numerous at-risk individuals are not benefitting from HIP. Research on providers' roles in the HIV Continuum of Care—linking clients to HIV testing, primary care, and support services—is lacking. This article helps fill this gap with evidence that providers exposed to EBIs, whose agencies offer EBIs, more frequently link clients to high-impact services. This is based on diffusion of innovations theory, where individuals in social networks influence one another's adoption of innovations. We hypothesize that providers are exposed to EBIs via training, reading and hearing about EBIs, and/or discussing EBIs with colleagues. We used cross-sectional data from 379 providers from 36 agencies in New York City. We used multilevel ordinal logistic regression models to test associations between provider exposure to EBIs (agency provides EBIs) and frequency of linkages to high-impact services. Providers exposed to greater numbers of EBIs more frequently link clients to HIV, hepatitis C (HEP-C), and sexually transmitted infections testing; to primary care; and to drug treatment and mental health services. Providers link clients most frequently to primary care and HIV testing and least frequently to HEP-C testing and syringe exchange. Findings suggest a dose effect, with exposure to more EBIs resulting in more linkages. Findings show a staged, evidence-based prevention approach that includes exposure to EBIs, leading to providers linking clients to high-impact services. There needs to be emphasis on inspiring providers to engage with high-impact services at the elevated levels needed to end the epidemic.